Physical, Chemical, Mineralogical, and Toxicological Characterization of Active and Inactive Tailings in the Arequipa Region, Peru - Navarro-Donoso, P (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Mining activity in Peru generates environmental liabilities with the potential to release toxic metals into the environment. This study conducted a comprehensive physical, chemical, mineralogical, and toxicological characterization of ten active and inactive tailings samples from the Arequipa region in southern Peru. Particle size distribution analysis, inductively coupled plasma atomic emission spectroscopy (ICP-AES), scanning electron microscopy with energy-dispersive spectroscopy (SEM-EDS), and the Toxicity Characteristic Leaching Procedure (TCLP) followed by ICP-MS were employed. The results revealed variable particle size distributions, with the sample of Secocha exhibiting the finest granulometry. Chemically, 8 out of 10 samples exhibited concentrations of at least two metals surpassing the Peruvian Environmental Quality Standards (EQS) for soils with values reaching >6000 mg/kg of arsenic (Paraiso), 193.1 mg/kg of mercury (Mollehuaca), and 2309 mg/kg of zinc (Paraiso). Mineralogical analysis revealed the presence of sulfides such as arsenopyrite, cinnabar, galena, and sphalerite, along with uraninite in the Otapara sample. In the TCLP tests, 5 out of 10 samples released at least two metals exceeding the environmental standards on water quality, with concentrations up to 0.401 mg/L for mercury (Paraiso), 0.590 mg/L for lead (Paraiso), and 9.286 mg/L for zinc (Kiowa Cobre). These results demonstrate elevated levels of Potentially Toxic Elements (PTEs) in both solid and dissolved states, reflecting a critical geochemical risk in the evaluated areas.
Keywords: mine tailings; geochemical characterization; toxicological analysis